Improved performance of UWB antenna by substrate perforation and slit notch - Zayd, Wessam; Ismail, Alyani; Mohad Isa, Maryam; Rahmatia, Suci (IEEE (IEEE Xplore), 2009)
In this paper a compact semi elliptical monopole ultra-wideband (UWB) antenna has been presented. A new technique to improve the performance of the antenna by perforation of the substrate with two circular holes was used. This perforation has significant effect to minimize the return loss in addition of using the existing techniques to improve the impedance bandwidth like notching off each of the patch and the ground plane. The simulation results show that the optimized design has an fractional bandwidth of 133% and bandwidth of 10.4 GHz starting from 2.6 GHz to more than 13 GHz with return loss batter than 10 dB and VSWR less than 2 with near Omni-directional radiation pattern over entire this band. The proposed antenna was fabricated. The measured return loss shows a good agreement with the simulation results.